P12 Evaluating policy responses to upstream determinants of chronic, non-communicable diseases: supporting healthy diets and active living in seven caribbean countries. (2nd September 2017) - Murphy, MM; Guell, C; Samuels, TA; Bishop, L; Unwin, N
Abstract : Background: In 2007, heads of government in the Caribbean Community (CARICOM) committed to concerted policy action to address non-communicable diseases, whose burden was recognised as a threat to regional development. In 2015, a large mixed-method evaluation study investigated the progress made in developing and implementing relevant policies. As part of this, a qualitative study in seven Caribbean countries aimed to identify, assess and compare existing policies, gaps in policy responses, and the factors influencing successful policy development and implementation. Methods: Policy document analysis was complemented by 76 semi-structured interviews with 80 relevant stakeholders in government, civil society and the private sector. Data collection and analysis protocols were developed iteratively. Interviews were audio-recorded and analysed pragmatically framed by the WHO NCD Action Plan, a Multiple Streams policy approach and realist evaluation principles. An analysis team coded using Dedoose software, after which two lead researchers synthesised the analyses. Results: Policy gaps existed regarding alcohol, diet and physical activity. Most widely reported successes across countries were policies and health promotion initiatives to support healthy eating in communities and in schools, including the development of dietary guidelines. Physical activity was targeted primarily in schools, with public participation in public sports events. Successful initiatives were often marked by collaboration between government ministries such as health, education and agriculture. There were very few existing policies around alcohol harm. The impact of these initiatives was reported as limited by adverse upstream determinants, including reliance on food imports entwined with the consequences of upholding existing trade agreements, which constrained more impactful fiscal and legislative action to support availability, quality and affordability of healthy foods. There was little evidence of policy responses to create physical and social environments conducive to active living, such as to support greater walking. The lack of focus on policy creation, lack of monitoring and evaluation of existing interventions, and limited staffing and financial capacities limited success in policy implementation. For alcohol specifically, national and political cultural attitudes and its economic importance deemed it untouchable from a policy standpoint. Conclusion: The least well developed policy responses concern upstream determinants of unhealthy diets, physical inactivity and alcohol harm. Local and regional political support is essential to accelerate action to support environments conducive to healthy eating and active living. Addressing reliance on food imports and existing trade agreements as well as developing and implementing policies to reduce alcohol related harm necessitates regional cooperation for a unified response.